Early Childhood Education and Development in Indonesia : An Assessment of Policies Using SABER - Denboba, Amina; Hasan, Amer; Wodon, Quentin (Washington, DC: World Bank, 2015)
Since the early 2000s, Indonesia has taken a number of steps to prioritize early childhood development – ranging from the inclusion of Early Childhood Development (ECD) in the National Education System Law No. 20 in 2003 to a Presidential Declaration on Holistic and Integrated ECD and the launch of the country’s first ever ECD Census in 2011. These policy milestones have occurred in parallel with sustained progress on outcomes included in the Millennium Development Goals, including for child malnutrition, child mortality and universal basic education. Additional progress could be achieved by strengthening ECD policies further. This report presents findings from an assessment of ECD policies and programs in Indonesia based on two World Bank tools: the ECD module of the Systems Approach for Better Education Results (SABER) and a guide on essential interventions for investing in young children. Results from the application of both tools to Indonesia are used to suggest a number of policy options for consideration.